PURCHASING DECISIONS IN TERMS OF LIFESTYLE, BRAND TRUST, WORD OF MOUTH AND PACKAGING Studies on the Hydroponic Community of Soloraya (Kohisora) - Hediono Hediono; Sudarwati Sudarwati; Ida Aryati; Agus Gunawan (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This study aims to determine and explain the influence of Lifestyle, Brand Trust, Word Of Mouth and Packaging on Purchasing Decisions in the Soloraya Hydroponic Community (Kohisora). This research uses a quantitative descriptive approach. The population in this study was infinite with a total sampling of 125 respondents. The sampling technique uses a non-random sampling method, namely purposive sampling. Data collection uses observation, documentation, questionnaires, and literature studies. Data analysis in this study includes validity test, reliability test, classical assumption test, multiple linear regression test and determination test. The results of data processing with the IBM SPSS 25.0 for windows program are Lifestyle, Brand Trust, Word Of Mouth and Packaging together or simultaneously have a significant effect on Purchasing Decisions in the Soloraya Hydroponic Community (Kohisora). Partially the variables Lifestyle, Brand Trust, Word Of Mouth have a positive and significant effect on the Purchase Decision, the Packaging variable has an insignificant positive effect on the Purchase Decision. The Purchase Decision variable can be explained by the variables Lifestyle, Brand Trust, Word Of Mouth and Packaging by 50.3% and the rest is influenced by other variables outside the study. Keywords : Lifestyle, Brand Trust, Word Of Mouth, Packaging, Purchasing Decision